Analysis of Students' Levels of Comfort, Ease, and Satisfaction With Digital-Based Assessments - Khairullah, Muhammad Fadhil; Hidayah, M. Salsabillah; Ahzami, M. Gita (Indonesian Journal of Teacher Education, 2025)
The development of digital technology has driven transformation in learning evaluation systems, including the implementation of digital-based assessment in higher education settings. This study aims to determine students' perspectives on digital assessment based on three main aspects: convenience, ease, and satisfaction. The research used a quantitative approach with a survey method thru the distribution of questionnaires to 43 students from various faculties. The data was analyzed descriptively to examine the frequency of responses for each statement indicator. The research results indicate that digital assessment is positively received by the majority of students, who also feel calm, focused, and not excessively pressured when taking digital assessments. Students found the digital assessment platform easy to access and the clear instructions simplified the completion process. Students feel the assessment process is more efficient, fair, transparent, and assessment results can be obtained quickly. Overall, digital assessment is considered effective, practical, and capable of supporting better learning evaluation processes compared to conventional methods. Nevertheless, improved technical stability for users who are not yet familiar is still needed to optimize the implementation of digital assessments.